Informatics in schools : improvement of informatics knowledge and perception : 9th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, ISSEP 2016, Münster, Germany, October 13-15, 2016, Proceedings /: improvement of informatics knowledge and perception : 9th International Conference on Informatics in Schools: Situation, Evolution, and Perspectives, ISSEP 2016, Münster, Germany, October 13-15, 2016, Proceedings. (2016) - Unknown
No abstract available